Assessment of the operating characteristics of brushless dc motors - Sarac, Vasilija (JET on-line, 2019)
This paper presents the operating characteristics of brushless DC motors (BLDC) obtained via analytical, numerical, and simulation software, enabling steady-state and transient characteristics of a motor to be computed. Based on the catalogue data from the producer, Moog, a motor is simulated in a closed-loop control system fed by a voltage inverter. The accuracy of the derived models is verified by comparison with data from the producer. The developed analytical and simulation models enable the studying of various motor operating modes, such as no-load, rated load, and locked rotor, including motor starting characteristics. They are universal and can be easily applied to any brushless DC motor by simple replacement of the motor parameters. A numerical model in FEM software verifies the accuracy of previously derived models by obtaining the motor operating characteristics and the magnetic flux density distribution in a cross-section of the motor. The results obtained from all models have verified the proper design of the motor and laid out the path for further improvement with respect to the various motor parameters or operating characteristics.
Keywords: brezkrtačni DC motorji; brushless DC motor; FEM model; transient characteristics; značilnosti